MANAJEMEN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI SMP MUHAMMADIYAH 29 PADANGSIDIMPUAN - Darliana Sormin (Universitas Muhammadiyah Tapanuli Selatan, 2017)
This study discusses the principal's management in improving the quality of education in midle school Muhammadiyah 29 Padangsidimpuan. The purpose of this study is to find out how the planning and implementation of school principals in improving the quality of education in midle school Muhammadiyah 29 Padangsidimpuan. The type of this research is qualitative descriptive by using interview, observation, and documentation as data collection. Analyze data by compiling data, managing data, then describing it systematically. The result of the principal's management in improving the quality of education at midle school Muhammadiyah 29 Padangsidimpuan is the principal conducting meetings to plan the annual program, then the results of the meeting will be socialized to teachers, students, parents and school committees, then in improving the quality of principals' Activities such as: pengajian, muhadarah by presenting ustadz, practice of prayer, then familiarize the students to be close to the Qur'an by doing activities one day one verse of a verse done in rotation and in reading every morning apple. Then in the process of learning the principal suggests that teachers use varied methods, discipline of the class entry schedule, the existence of job accountability, deliberation in deciding a problem, openness in terms of costing fees and development money